A representação de professores de educação física sobre sua docência em creches e Núcleos de Educação Infantil (NEIs) - Mattos, Aretuza Suzay (2012)
The human subjectivity is manifested as well in the educational action, it is set as an important factor in the teaching process understanding. The representation, perception and imagination are aspects that can be redeemed in the teacher s discourses, providing opportunities for the understanding of concepts that divide, reduce, facilitate or interdict the pedagogical act. In day-care center, these concepts are the topic of researches that criticize, mainly, the transfer of physical education based on primary schools standards, for this stage of education, without taking into account the specific needs and development of 0-5 years children. This research aims to study and analyze the representation of the physical education teacher, about their practice in the day care centers and childhood education centers (CECs). In this way, it was employed a field research through non-directive interviews with eight physical education teachers who work in Florianópolis city. Some significant excerpts were extracted from the interviews, which reveal the projection, identification and transferring in the direction of the goals and content of the classes of these teachers. It is concluded that the experiences influence the perception, the meanings representations that interfere in the concepts of the subjects on their educational role and their views on the body and movement.